2017
DOI: 10.1021/acsnano.7b00093
|View full text |Cite
|
Sign up to set email alerts
|

Engineering an Injectable Muscle-Specific Microenvironment for Improved Cell Delivery Using a Nanofibrous Extracellular Matrix Hydrogel

Abstract: Injection of skeletal muscle progenitors has the potential to be a minimally invasive treatment for a number of diseases that negatively affect vasculature and skeletal muscle, including peripheral artery disease (PAD). However, success with this approach has been limited because of poor transplant cell survival. This is primarily attributed to cell death due to extensional flow through the needle, the harsh ischemic environment of the host tissue, a deleterious immune cell response, and a lack of biophysical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 30 publications
1
55
0
Order By: Relevance
“…Therefore, the measured value of 75.77 ± 13.16 mmol reduced glutathione equivalent/mg from our myocardial matrix material contributes a high concentration of free thiols that can greatly exceed the ROS scavenging capability found in the native myocardium alone. This is particularly evident in our in vitro oxidative stress assay, and previously reported results 22 , where encapsulated cardiomyocytes were shielded from the oxidative stress from H2O2 at millimolar concentrations while micromolar concentrations are able to induce extensive cell death for standard 2D cardiomyocytes cultures 32 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Therefore, the measured value of 75.77 ± 13.16 mmol reduced glutathione equivalent/mg from our myocardial matrix material contributes a high concentration of free thiols that can greatly exceed the ROS scavenging capability found in the native myocardium alone. This is particularly evident in our in vitro oxidative stress assay, and previously reported results 22 , where encapsulated cardiomyocytes were shielded from the oxidative stress from H2O2 at millimolar concentrations while micromolar concentrations are able to induce extensive cell death for standard 2D cardiomyocytes cultures 32 .…”
Section: Discussionsupporting
confidence: 77%
“…For assessment of cell proliferation, cells were pre-labeled by CellTrace TM Far Red (ThermoFisher Scientific) before encapsulation while other cellular experiments proceeded with unlabeled cells. Encapsulation of cells was performed with some protocol modifications to previously described protocols for improving viability for this specific cell type 22 . In brief, solely neutralized myocardial matrix in lyophilized aliquots were resuspended to a 6mg/mL concentration with culture media consisting of 1:1 DMEM/F12 solution (Gibco) supplemented with 10% fetal bovine serum (Gibco) and 1% penicillin streptomycin (Gibco).…”
Section: Neonatal Cardiomyocyte Isolation and Hydrogel Encapsulationmentioning
confidence: 99%
“…Successful delivery of transplanted cells and maintenance of cell viability after transplantation are common challenges faced by many cell-based therapies (7,17,42,43). As the dosage and retention of delivered viable cells have been correlated with symptomatic outcomes for a variety of injury and disease models, the inability to successfully transplant cells directly into damaged tissue is a significant hurdle for clinical translation of many potential regenerative medicine therapies (42)(43)(44)(45)(46). Here, we specifically address the challenge of SC delivery for SCI through the design of a novel biomaterial strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, many groups have adapted ECM hydrogels for regenerative medicine applications, using the ECM from the same tissue type which they are aiming to regenerate [3]. The importance of tissue specificity has been explored in vitro through comparison between single ECM components [13,40] and ECM combinatorial screening approaches [41]. Lately, groups have been comparing ECM derived from different decellularized organs and have found that there are important tissue specific effects in vitro [9,14,16,17].…”
Section: Discussionmentioning
confidence: 99%